(untitled) (Universal International Scientific Journal, 2026)
This thesis analyzes the problem of automatic subtitle generation for video content within the field of computational linguistics. In the digital media environment, the leading role of video content in information dissemination has significantly increased the demand for automatic subtitling technologies. The study examines automatic speech recognition (ASR), natural language processing (NLP), and text-to-visual adaptation processes as an integrated system. Based on statistical data, the audience consuming information through video is analyzed, and the social and educational significance of automatic subtitles is substantiated